PENGARUH CITRA MEREK, WORD OF MOUTH DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI DI KOTA BATAM - Yulyanti; Sitorus , David Humala (LPPM Universitas Putera Batam, 2025)
The purpose of this study is to examine the influence of brand image, word of mouth, and product quality on the purchasing decision of Xiaomi smartphones in Batam. This research adopts a quantitative approach using a survey questionnaire as the data collection tool. The sample was selected using purposive sampling technique, with a total of 100 respondents. Data processing was done using SPSS 30. Descriptive statistical analysis was employed to describe the characteristics of the respondents, while multiple linear regression analysis was used to test the relationships between variables. The findings of this study indicate that brand image, word of mouth, and product quality have a significant impact on the purchasing decision of Xiaomi smartphones in Batam.